Analisis Manajemen Layanan TI Pada Perusahaan Penyedia Layanan Internet Menggunakan ITIL V4 Service Value System - Irmawati Tri Wahyuni; Andini Diyas Saputri; Ito Setiawan; Banu Dwi Putranto (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This study analyzes the gap in the implementation of Information Technology IT service management at an internet service provider in Purwokerto using the ITIL V4 Service Value System SVS framework. The company faces a number of major problems, such as delays in incident handling, data fragmentation between operational applications, low automation in network monitoring, and suboptimal coordination between the technical and customer service divisions. The purpose of this study is to evaluate the level of compliance of current service practices with ITIL V4 SVS best practices and to formulate recommendations for improvements that can increase operational efficiency and service reliability. The research uses a qualitative descriptive method with a case study approach, with data collected from interviews and observations in the technical and customer service divisions, then analyzed based on the five main components of ITIL V4 SVS. The results show that the company has implemented several ITIL principles, particularly in terms of customer value focus and process simplicity, but the implementation of iterative feedback, data integration, and automation is still at a low level of maturity. This study concludes that strengthening the real-time monitoring system, increasing cross-divisional visibility, and establishing a Continual Improvement Register are important steps towards realizing more efficient, responsive, and sustainable IT service management.